Women’s fear of normal delivery and their decision on the mode of delivery: a cross-sectional study - Sarker, Anima; Chowdhury, Shamima Haque; Begum, Mosammat Shahina; Bhowmik, Juthi; Islam, Mohammad Shaiful (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Caesarean section, C-section, or caesarean birth is the surgical delivery of a baby through a cut (incision) in the mother's abdomen and uterus. It's a surgical procedure utilized when a vaginal delivery isn't possible or safe, or when the health of the mother or infant is at risk. Caesarean section rates range from 0.4 to 40% in different countries, and the trend has been growing over the previous 30 years. These increases have been linked to a number of factors. The purpose of this study was to learn more about these factors in the context of Bangladeshi demographics. Aim of the study was to investigate the women’s Fear of normal delivery and their decision on the mode of delivery Methods: This cross-sectional observational study was conducted at the department of obstetrics and gynecology in Uttara Adhunik medical college and hospital, Bangladesh. The study duration was from 1February 2021 to 30 November 2021. The present study was carried out with a total of 63 women who had undergone caesarean section during the study period. A convenient sample selection method was done for the selection of the participants Result: Among the participants of the present study, 47.62% were aged between 25-29 years, 76.19% were Muslims, and 76.19% stayed at the hospital for 3-4 days. 90.48% had been pregnant for 36-40 weeks. Lower abdominal pain and labor pain was observed in 20.63% of the participants. The majority of the participants underwent caesarean delivery due to fear of labor pain and episiotomy. Conclusion: The fear of childbirth or labor pain is the most common cause in patients undergoing caesarean section, followed by doctor advice due to medical comorbidities and fear of episiotomy.